Membangun Jiwa Kepemimpinan Adaptif dan Kolaboratif pada Mahasiswa BEM Teknik 2025 - wijaksono, agus; Andi Wapa (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Leadership issues within student organizations often manifest as low adaptability to change, weak inter-divisional communication, and poor collaboration skills. These challenges reduce organizational effectiveness and hinder the holistic development of student leadership. To address this, a community service program was conducted to foster adaptive and collaborative leadership among the 2025 board members of the Student Executive Board (BEM) of the Faculty of Engineering, Universitas Bakti Indonesia. The training took place on May 28, 2025, at Vinus Tourism Area, Songgon, Banyuwangi, using an experiential learning approach that combined theoretical concepts with practical application through indoor and outdoor activities. The program included leadership theory sessions, case discussions, team problem-solving simulations, an outbound leadership challenge, and individual and group reflection. Evaluation was conducted through pre-tests, post-tests, observations, and participant reflections. Results showed a 24.4% average increase in post-test scores, particularly in understanding adaptive leadership, collaborative ability, and readiness to face organizational dynamics. Behavioral changes were also evident, including improved listening, crisis readiness, and greater awareness of cross-divisional teamwork. Visual documentation and participant reflections confirmed the program’s transformational impact. This training effectively shaped student leadership that is participatory, contextual, and relevant to 21st-century challenges. Similar programs are recommended to be held regularly, accompanied by post-training mentoring and expansion to other student organizations for broader and more sustainable impact.